Community structure and plant diversity under different degrees of restored grassland in mining areas of the Qilian Mountains, Northwestern China - Yang, Xiaomei; Feng, Qi; Liu, Wei; Xia, Honghua; Zhang, Jutao; Yang, Linshan; Zhang, Chengqi; Wang, Zhiyang; Feng, Yonglin (Frontiers in Environmental Science, 2023)
Background: Mining activities are known to exert significant effects on the structure and function of grassland ecosystems. However, the role of mining grasslands restoration in altering the plant community and soil quality remains poorly understood, especially in alpine regions. Here, we investigated ecosystem stability and species diversity in grasslands with dynamic changes and different restoration levels in the Tianzhu alpine mining area locating in the Qilian Mountains. Methods: The plant community structure and species composition of the grasslands with different restoration levels were analyzed by the sample method. We used five different restoration levels: very low recovered degree (VLRD), low recovered degree (LRD), medium recovered degree (MRD), and high recovered degree (HRD), and selected natural grassland (NGL, CK) as the control. Results: Plant community structure and species composition were significantly higher than those under the VLRD in the Tianzhu alpine mining area (P < 0.05), with HRD > MRD > LRD>VLRD. There were 11 families, 18 genera, and 17 species of plants, mainly in the families of Leguminosae, Asteraceae, Gramineae, Rosaceae, and Salicaceae; among them, Salicaceae and Gramineae played decisive role in the stability of the community. The ecotype community showed that perennial herbaceous plants were the most dominant, with annual herbaceous plants being the least dominant, and no tree and shrub layers were observed; the dominance index was the highest in VLRD at 0.32, the richness index was the highest in HRD at 2.73, the diversity of HRD was higher at 1.93, soil pH and EC showed a decreasing trend, and SMC, SOC, TN, NO3-N, NH4-N, AN, TP, and AP content showed increasing trend with the increase of grassland restoration. Conclusion: In conclusion, with the increase of restored grassland in the Tianzhu alpine mining area, plant diversity gradually increased and plant community structure gradually diversified, which were close to plant diversity of NGL. The protection of partially VLRD and LRD grasslands in the mining area should be emphasized, and the mine grassland should be used rationally and scientifically restored.